Sequence analysis of a "true" chalcone synthase (chs_H1) oligofamily from hop (Humulus lupulus L.) and PAP1 activation of chs_H1 in heterologous systems - Matousek, Jaroslav; Vrba, Lukás; Skopek, Josef; Orctova, Lidmila; Pesina, Karel; Heyerick, Arne; Baulcombe, David; De Keukeleire, Denis (Journal of agricultural and food chemistry, 2006)
Screening of a cDNA library of the hop cv. Osvald's 72 and genomic cloning were used to isolate members of an oligofamily of chs_H1 genes that codetermine the biosynthesis of prenylated chalcones known to be valuable medicinal compounds present in hop (Humulus lupulus L.). chs_H1 oligofamily members showed more than 99% and 98% identity on nucleotide and amino acid levels, respectively, and retained all conserved amino acids that form the catalytic center characteristic for "true" chalcone synthases. The chs_H1 promoter exhibited low sequence variability in addition to conservation of all predicted cis-regulatory elements. Possible transactivation of the chs_H1 gene with the transcription factor PAP1 from Arabidopsis thaliana was assayed using Agrobacterium tumefaciens infiltrations of Nicotiana benthamiana and Petunia hybrida plants. Infiltration of N. benthamiana leaves with chs_H1 promoter/GUS chimeras led to a 24.8-fold increase of the GUS activity when coinfiltrated with the pap1 gene. Coinfiltration of the "native" chs_H1 gene with pap1 led to an increased accumulation of chs_H1 mRNA as observed by semiquantitative reverse transcription-polymerase chain reaction. Transgenic lines of P. hybrida expressing the pap1 gene showed unusual patterns of UV-A-inducible pigmentation and anthocyanin accumulation in parenchymatic and medulla cells. Infiltration of transgenic leaves of P. hybrida with chs_H1 and pap1 genes arranged as a tandem led to quick pigmentation within 12 h after UV-A irradiation. It is indicated that the chs_H1 promoter contains functional element(s) mediating an efficient response to PAP1 expression and UV-A irradiation. UV-A also induced chs_H1 mRNA and accumulation of flavonol glycosides in hop leaves. It can be expected that the PAP1 factor could significantly influence the expression of the chs_H1 oligofamily in transgenic hop and modify the hop metabolome.
Keywords: Amino Acid Sequence; aktivace enzymů; Enzyme Activation; molekulární sekvence - údaje; listy rostlin; sekvence nukleotidů; Molecular Sequence Data; sekvence aminokyselin; Transcription Factors; anthokyaniny; Humulus; acyltransferasy; Plant Leaves; Anthocyanins; Plants, Genetically Modified; Pancreatitis-Associated Proteins; Ultraviolet Rays; proteiny huseníčku; RNA, Messenger; Acyltransferases; Arabidopsis Proteins; ultrafialové záření; Base Sequence; transkripční faktory; geneticky modifikované rostliny; polymerázová řetězová reakce s reverzní transkripcí; proteiny asociované s pankreatitidou; Reverse Transcriptase Polymerase Chain Reaction; messenger RNA